2008
DOI: 10.1159/000144038
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Shrimp Tropomyosin-Specific Hypersensitivity in Mice

Abstract: Background: Shellfish hypersensitivity is amongst the most common food allergies. The major shellfish allergen was identified as tropomyosin. Here, we investigated the immediate hypersensitivity responses, IgE and cell-mediated immune response in mice sensitized with recombinant shrimp tropomyosin. Methods: Shrimp tropomyosin was cloned and expressed as a His-tagged fusion recombinant protein in Escherichia coli. Three- to 4-week-old BALB/c mice were sensitized by intragastric administration of recombinant tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 89 publications
(68 reference statements)
0
30
2
3
Order By: Relevance
“…There are 3 previous elegant studies that reported on the development of shrimp allergy and 1 on mud crab allergy using mouse models with BALB/c and C3H/HeJ mice [25,26,27,28]. Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are 3 previous elegant studies that reported on the development of shrimp allergy and 1 on mud crab allergy using mouse models with BALB/c and C3H/HeJ mice [25,26,27,28]. Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC. Lam et al [25] and Leung et al [26] reported another shrimp tropomyosin allergy model using recombinant protein and BALB/c mice using intragastric exposure with cholera toxin adjuvant [25,26]. Readouts of allergenicity included sIgE responses (OD values; no titers), spleen-cell IL-4 responses, oral allergen-induced symptom scores and histopathological changes in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the major shrimp allergen tropomyosin has been characterized, clinical trials for shrimp allergy AIT are still lacking. Here, we adopted a well-established mouse model that mimics the clinical responses in shrimp allergic patients [10], in order to investigate the dose-response effect of AIT with recombinant (r) shrimp tropomyosin from Metapenaeus ensis , i.e., rMet e 1, in treatment. …”
Section: Introductionmentioning
confidence: 99%